Anaesthetic Management of Severe Head Injuries at Chu-Kara - Mouzou, Essohanam (British Journal of Healthcare and Medical Research, 2024)
The aim of the study was to take stock of the management of severe head trauma (SCT) at the CHU-Kara. This was a retrospective descriptive and analytical study carried out in the surgical intensive care unit of CHU-Kara from 1 January 2021 to 31 December 2023. 185 patients were studied. The sex ratio was 4.6. The average age was 34.68±18.78 years. Farmers were most affected (28.97%), followed by pupils and students (22.76%). The majority of patients (63.78%) came from the outskirts of Kara. Road accidents were the main cause (86.49%). Two-wheelers were involved in 96.87% of cases. 64.52% of patients had not worn a helmet. All patients had received non-medical transport. On admission, 86.65% had a Glasgow score ≤ 8. Fever and hyperthermia were present in 42.16% of cases ; 32.05% had presented with hypoxaemia. Lesions associated with TCG were found in 28.11% of cases with limb involvement. Anaemia was found in 36.75% of cases. CT lesions were dominated by cerebral contusions in 27.56% of cases. 45.95% of patients were treated within one hour. 98.37% of patients were treated medically. Complications occurred in 5.41% of cases and mortality was 69.73%. MCTs had a high mortality rate. The introduction of emergency medicine would considerably reduce this mortality rate.